Blood Products Provided to Patients Receiving Futile Critical Care. Issue 9 (1st September 2017) - Neville, Thanh H.; Ziman, Alyssa; Wenger, Neil S.
Abstract : The number of hospitalized patients receiving treatment perceived to be futile is not insignificant. Blood products are valuable resources that are donated to help others in need. We aimed to quantify the amount of blood transfused into patients who were receiving treatment that the critical care physician treating them perceived to be futile. During a 3‐month period, critical care physicians in 5 adult intensive care units completed a daily questionnaire to identify patients perceived as receiving futile treatment. Of 1136 critically ill patients, physicians assessed 123 patients (11%) as receiving futile treatment. Fifty‐nine (48%) of the 123 patients received blood products after they were assessed to be receiving futile treatment: 242 units of packed red blood cells (PRBCs) (7.6% of all PRBC units transfused into critical care patients during the 3‐month study period); 161 (9.9%) units of plasma, 137 (12.1%) units of platelets, and 21 (10.5%) units of cryoprecipitate. Explicit guidelines on the use of blood products should be developed to ensure that the use of this precious resource achieves meaningful goals.